77 Three Dimensional And Histological Study Of The Equine Superficial Digital Flexor Tendon. (5th September 2014) - Ali, Othman; Clegg, Peter; Comerford, Eithne; Canty-Laird, Elizabeth
Abstract : Introduction: The equine superficial digital flexor tendon (SDFT) is a complex hierarchal structure that transmits force from muscle to bone and stores energy by its stretching and recoiling function 1, 2, 3 . The aim of this study was to describe the three-dimensional (3D) anatomy of this tendon and further to evaluate its histological architecture: specifically to determine the organisation of the individual sub-units (fascicles) and how this may vary between individuals and during ageing. Methods: 1-Image processing: Normal SDFT were obtained from different aged horses, wrapped in foil and frozen (-20C). The frozen SDFT samples were sectioned transversely; the thickness of the slices varied between 2–3 mm and each section was photographed using a Canon EOS 5D Mark III camera (100 mm focal length). Dedicated software (Corel PaintShop Pro X4) was used to convert raw images into grey scale Tiff images which were then processed through ImageJ and IMOD to obtain better contrast and create a 3D model of the macroscopic tendon fascicular structure. 2-Histological scoring: The specimens from three different regions (proximal, mid metacarpal and distal) of different ages (from foetal to 20 years old) were fixed in 4% paraformaldehyde, pH 7.4, at room temperature and dehydrated overnight. The specimens were embedded in paraffin and sectioned to 5-μm-thick (longitudinally), on polylysine slides and stained with Haematoxylin and Eosin. A scoring method was developed to define specific tendon structural features and used to describe how these features were altered with age. Results: Fascicles were defined as being delineated by a well-defined interfascicular septum which is further subdivided into secondary sub fascicles with a thinner endotenon when they were measured using ImageJ 4 (Figure 1 ). The numbers of the secondary and tertiary fascicles were not constant and they are progressively increased from the proximal to distal regions of the tendon. Furthermore, specific fascicles either terminated or branched progressively from the proximal to distal region through the tendon (Figure 2 ). The tissue histology parameters including fascicular angulation, interfascicular thickness and the cellular morphology were found to be altered with age. Conclusion: We conclude that the secondary and tertiary fascicles display a complex 3D organisation not reflected in current models of the hierarchical organisation of equine tendon. Some histological parameters were found to be altered with ageing. In particular we demonstrated that some fascicles are discontinuous within a tendon, whilst others demonstrate a branching pattern. Understanding the 3-dimensional anatomy of tendon will facilitate understanding of tendon structure-function relationships, age-related changes and injury predisposition. References: Benjamin et al . J Anat. 2008;212:211–228 Fallon et al . J Orthop Res. 2002;20:920–926 Kannus, Scand J Med Sci Sports. 2000;10:312–320 Kastelic et al . Connect. Tissue Res. 1978;6:11–23 Meghoufel et al . Med Pmhys. 2010;37:1038